[tex]3 \sqrt{2} x - 6 = 0 \\ 3 \sqrt{2} x = 6 \\ x = \frac{6}{3 \sqrt{2} } \\ x = \frac{2}{ \sqrt{2} } \\ x = \frac{2 \sqrt{2} }{ \sqrt{2} \times \sqrt{2} } \\ x = \frac{2 \sqrt{2} }{2} \\ x = \sqrt{2} [/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
[tex]3 \sqrt{2} x - 6 = 0 \\ 3 \sqrt{2} x = 6 \\ x = \frac{6}{3 \sqrt{2} } \\ x = \frac{2}{ \sqrt{2} } \\ x = \frac{2 \sqrt{2} }{ \sqrt{2} \times \sqrt{2} } \\ x = \frac{2 \sqrt{2} }{2} \\ x = \sqrt{2} [/tex]